ANALYSIS OF RISK FACTORS ASSOCIATED WITH HAND ARM VIBRATION SYNDROME (HAVS) COMPLAINTS AMONG WORKERS AT PT BEURATA SUBUR PERSADA (BSP) IN NAGAN RAYA IN 2025 - Fitri, Nasyhwaa rahma; Wahyuni, Susy Sri; Saputra, Firman Firdauz; Alamsyah, Teuku; Is, Jun Musnadi (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2026)
In palm oil mill processing companies, workers do a lot of activities using tools and machines that have a high frequency of vibration so that there is a risk of Hand Arm Vibration Syndrome (HAVS) complaints in PT Beurata Subur Persada (BSP) Nagan Raya workers. This study aims to analyze the risk factors associated with HAVS complaints in workers at PT Beurata Subur Persada Nagan Raya. This research method uses quantitative analytics with a crossectional design. The results of bivariate analysis showed that age was associated with HAVS complaints p-value=0,05 while the last level of education p-value=0,99, unit/section p-value=0,31, and knowledge p-value=0,22 were not associated with HAVS complaints. Based on these results, the company is expected to provide safety antivibration gloves that meet safety stnadards and pay attention to comfort aspects, schedule regular health screenings for each worker so that they can detect HAVS complaints early.